PERANCANGAN SISTEM INFORMASI ARSIP SURAT MASUK DAN KELUAR BERBASIS WEBSITE PADA KOMISI PEMILIHAN UMUM KABUPATEN KUNINGAN - purnamasari, wulan; Gina Dewi Sonia (Jurnal Fakultas Teknik Kuningan, 2024)
Increasingly advanced technological developments have an impact on increasing human needs for information. Information is very important in an organization because information is fundamental in carrying out every activity so that the activity can run as expected. Information can be obtained from various sources, one of which is written information, namely letters. Various kinds of documents and media have been created to make it easier for humans to store, search and disseminate information. These documents are better known as archives, which means a record of activities or sources of information that is stored systematically so that when needed it can be used as a reference in carrying out activities. Therefore, to overcome existing problems while supporting a system that is moving towards rapid technological development, a website-based archiving application is needed to support the archiving needs of the Kuningan Regency General Election Commission. It is hoped that this application can make it easier for the General Election Commission to manage its archiving system.